2007
DOI: 10.1007/s00520-007-0285-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acculturation on the use of traditional Chinese medicine in newly diagnosed Chinese cancer patients

Abstract: Prevalence and type of use were found to vary as a function of the degree of acculturation. Health care practitioners would be well advised to discuss TCM/CAM use with their patients, especially those who are less acculturated to Western society, since they are the most likely users of TCM/CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
18
1
Order By: Relevance
“…Studies of Chinese immigrants have shown that the combined use of the two types of medicine is common in the U.S. and in Canada and that traditional over the counter remedies and treatments are often sought (Ferro et al 2007;Lai and Chappell 2007;Ma 2004;Wu et al 2007). Studies focusing on Korean and Vietnamese immigrants have shown similar results (Jenkins et al 1996;Kim et al 2002;O'Callaghan and Quine 2007;Pang 1989).…”
Section: Traditional Medicinementioning
confidence: 96%
“…Studies of Chinese immigrants have shown that the combined use of the two types of medicine is common in the U.S. and in Canada and that traditional over the counter remedies and treatments are often sought (Ferro et al 2007;Lai and Chappell 2007;Ma 2004;Wu et al 2007). Studies focusing on Korean and Vietnamese immigrants have shown similar results (Jenkins et al 1996;Kim et al 2002;O'Callaghan and Quine 2007;Pang 1989).…”
Section: Traditional Medicinementioning
confidence: 96%
“…Despite this growing diversity, limited research has examined the impact of ethnicity on CAM use among immigrants [18][19][20][21][22]. These studies indicated that ethnic differences and cultural factors influence the frequency and type of CAM used in adults; with herbal medicine, a form of traditional Chinese medicine (TCM), being mostly used by Chinese people [18][19][20][21][22]. Chinese individuals were of particular interest to our research team because they were the largest visible minority group in Canada in the 2006 Census [23].…”
Section: Introductionmentioning
confidence: 99%
“…Asian Americans reported higher rates of CAM use (31.8%) compared to other minority ethnic groups (African Americans - 20.1%; Hispanics-16.9%) [1]. Among Chinese immigrant cancer patients in the West, use of CAM is as high as 47% [2]. Traditional Chinese Medicine (TCM), a subset of CAM, is commonly used in East Asia as a complementary treatment among Chinese cancer patients receiving conventional treatment [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…25% of Chinese patients reported CAM use, and were more likely to use herbs than any other ethnic group [8]. In Canada, Ferro et al studied newly diagnosed Chinese cancer patients and found that 47% used CAM; herbal remedies were most common (61%) [2]. In a California study, using the regional tumor registry (operated by the Northern California Cancer Center), of the prevalence of concurrent use of conventional and alternative treatments for cancer by ethnicity (Chinese, Latino, White, Black), Lee et al found that among 379 breast cancer patients, 48% used at least one type of CAM and approximately 1/3 used 2 types after being diagnosed [9].…”
Section: Introductionmentioning
confidence: 99%